Archaeorhizomycetes Spatial Distribution in Soils Along Wide Elevational and Environmental Gradients Reveal Co-abundance Patterns With Other Fungal Saprobes and Potential Weathering Capacities - Pinto-Figueroa, Eric Alejandro; Seddon, Emily; Yashiro, Erika; Buri, Aline; Niculita-Hirzel, Hélène; van der Meer, Jan Roelof; Guisan, Antoine (Frontiers in Microbiology, 2019)
Archaeorhizomycetes, a widespread fungal class with a dominant presence in many soil environments, contains cryptic filamentous species forming plant-root associations whose role in terrestrial ecosystems remains unclear. Here, we apply a correlative approach to identify the abiotic and biotic environmental variables shaping the distribution of this fungal group. We used a DNA sequencing dataset containing Archaeorhizomycetes sequences and environmental variables from 103 sites, obtained through a random-stratified sampling in the Western Swiss Alps along a wide elevation gradient (> 2,500 m). We observed that the relative abundance of Archaeorhizomycetes follows a ‘humped-shaped’ curve. Fitted linear and quadratic generalized linear models revealed that both climatic (minimum temperature, precipitation sum, growing degree-days) and edaphic (carbon, hydrogen, organic carbon, aluminum oxide and phyllosilicates) factors contribute to explaining the variation in Archaeorhizomycetes abundance. Furthermore, a network inference topology described significant co-abundance patterns between Archaeorhizomycetes and other saprotrophic and ectomycorrhizal fungal taxa. Overall, our results provide strong support to the hypothesis that Archaeorhizomycetes in this area have clear ecological requirements along wide, elevation-driven abiotic and biotic gradients. Additionally, correlations to soil redox parameters, particularly with phyllosilicates minerals, suggest Archaeorhizomycetes might be implied in biological rock weathering. Such soil taxa-environment studies along wide gradients are thus a useful complement to latitudinal field observations and culture-based approaches to uncover the ecological roles of cryptic soil organisms.